Narrative medicine in the framework of empirical social research: the Russian context - Vitaly Lekhtsier; Anna Gotlib (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2017)
This article contains the results of the empirical analysis carried out in 2012-2016 which sought to examine whether patients' narratives of their illness were present in doctor-patient communication and whether this subjective story was significant to both sides of the medical communication in Russian somatic disease medicine. The research was carried out in four stages and combined qualitative and quantitative methods, analyzing the perspectives of patients, doctors and medical students through surveys and interviews as well as looking at online doctor-patient communication in health forums. In all four stages, the results of the research showed that little value was placed on the subjective experience of disease in doctor-patient interactions. The topic of narrative medicine is new to Russian social studies, making the results of this research an important contribution to the establishment of narrative medicine as a global idea advocating the universal therapeutic and ethical value of patients' stories of illness in the "remission society," in which chronic pathologies dominate.